How to improve speaking skills without living in a native condition - Otajonova Kamola (Zien Journals, 2023)
Reading and speaking are two fundamental skills that we use to communicate, and they are closely related. A study of the relationship between movies, speech, and reading shows how they affect and how closely they are related to each other.
Keywords: learning English; communication; films